High-Flow Nasal Cannula Oxygen Therapy in A Palliative Care Context at Home, a New Opportunity? A Palliative Care Team Experience - Fonseca, Marta (2022)
Dyspnoea is one of the more common symptoms in advance stages of several diseases and its control is crucial for patient comfort. Supplementary oxygen therapy plays an important role on that. In the last years, the use of high-flow nasal cannula oxygen therapy (HFNC) in palliative care has been developed. We present three cases of patients accompanied by the Palliative Care Team who used HFNC for dyspnoea control and the team’s effort for organizing domiciliary use of it. All patients showed a better quality of life, in what concerns dyspnoea, and the use of opioid therapy was reduced. The presence of the Palliative Care Team was essential for the patient, family and domiciliary care team’s support. HFNC seems to be a possible secure and effective resource in the management of respiratory symptoms in the palliative patient, along with pharmacological and non-pharmacological strategies.